Oral Candidiasis and Novel Therapeutic Strategies: Antifungals, Phytotherapy, Probiotics, and Photodynamic Therapy - Contaldo, Maria; Di Stasio, Dario; Romano, Antonio; Fiori, Fausto; Della Vella, Fedora; Rupe, Cosimo; Lajolo, Carlo; Petruzzi, Massimo; Serpico, Rosario; Lucchese, Alberta (Current Drug Delivery, 2023)
Oral candidiasis is an opportunistic infection of the oral mucosa sustained by fungi of the genus Candida. Various Candida species, with a predominance of C. albicans, normally a saprophyte of the oral cavity, may become virulent and infect the oral mucosa with variegated clinical presentation, in case of imbalance of the oral microbiota, the presence of local predisposing factors and systemic conditions that weaken the immune system. Conventionally, oral candidiasis eradication is done with the help of antifungal drugs. However, the growing phenomena of drug resistance and the increase in infections sustained by non-albicans species being less responsive to common antifungals have orientied researches towards the experimentation of alternative therapies. The present review considered the most promising alternative therapeutic proposals. The use of plant derivatives with phytotherapy is a promising option, such as probiotics, to rebalance the oral microbiota in case of dysbiosis. Finally, antimicrobial photodynamic therapy (aPDT), with highly selective fungicidal activity and free of side effects, is also being studied as a powerful alternative to drug administration. All these therapies are alternatives or supportive to the conventional treatment of recurrent and non-drug-responsive forms of oral candidiasis. However, further studies are needed to define the most active compounds, the efficacy of the therapies compared with the conventional ones, and the planning of regulated and standardized protocols.
Keywords: denture stomatitis